Contrasting Along-Slope vs. Downslope Sedimentation Style on the High-Latitude Eastern Canadian Continental Margin During the Last 40 ka - Rashid, Harunur; He, Jianing; Patro, Ranjan; Brown, A. Owen (Frontiers in Earth Science, 2022)
Late Pleistocene Labrador Sea depositional systems developed in front of ice streams and glacier outlets from the Laurentide Ice Sheet (LIS) are documented by Huntec and 3.5 kHz seismic profiles and piston cores. Due to efficient grinding by the LIS, massive amounts of fine-grained sediments and meltwater in addition to the icebergs linked to the Heinrich events (H events) of the last glaciation were delivered to the neighboring Labrador Sea. The position of the Hudson Strait ice stream during the periodic expansion and contraction on the Labrador margin allowed fine-grained sediments and meltwater direct delivery on the lower shelf and upper slope. These discharges were then transported southward by the Labrador Current and western boundary current. In contrast to the lower shelf and upper slope, sediments delivered on the mid to the lower Labrador Slope were transported by the Northwest Atlantic Mid-Ocean Channel to distal sites. The nepheloid flow layer at or near the sea bottom or at mid-water depths developed from meltwater loaded with an excessive charge of fine-grained sediments. Contrastingly, the non-discriminatory ice rafting process delivered detritus of all sizes, but its total contribution to the sediment column was only minor, notwithstanding its paleoclimatic significance during H events. Heinrich H1, H2, and H4 layers were identified by their characteristic nepheloid flow layer deposits, that is, alternating coarse silt and clay-sized laminae with thin ice-rafted debris interspersed by coarse- to fine-grained dropstone. Furthermore, the progressive thinning and eventual disappearance of the fine-laminae (i.e., coarse and fine silt/clay) in H layers at the distal sites suggest the exhaustion and raining out of fines due to long-distance transport. However, the H3 layer was identified by a combination of nepheloid flow layer deposits (upper slope) and finely laminated mud turbidites (lower slope and deep basin) at proximal sites. In the lower Labrador Slope and Basin, the H3 stratigraphic equivalent layer was identified by exorbitantly thick finely laminated carbonate-rich mud turbidites. The divergent sedimentation style (i.e., reflected by the sediment facies) and the thickness of the H3 layer compared to other H events suggest that the Hudson Strait ice stream position was different from other H events. Therefore, our data imply that the divergence in the H3 layer between the eastern and western North Atlantic might lie with the position of the Hudson Strait ice stream on the Labrador continental margin.